The Effect of Limestone Substitution as Cement and Plastic Waste Slike Aggregate Slike on the Compressive Strength of Concrete - Acep Hidayat; Alan Bandangan (NAROTAMA UNIVERSITY, Indonesia, 2021)
With the development of concrete technology in these days, concrete innovation is needed because it does not rule out the possibility of this concrete material, namely fine aggregate, coarse aggregate, cement, and water, which is decreasing over time or thinning. An innovation is needed that can reduce the use of cement by using other materials, so that the amount of cement usage can be reduced. Examples of innovation as a material that can be mixed with concrete include fly ash, palm ash, extinguished lime, bagasse ash and others. This is what drives research for concrete mixtures other than sand, gravel, cement and water, adding materials to the concrete mixture, namely limestone as a substitute for cement and plastic waste as a substitute for coarse aggregate. The use of limestone is expected to reduce cement levels and the use of plastic waste can reduce the use of gravel from river stones so as not to damage the river ecosystem. The addition of limestone and plastic waste is expected without reducing the strength of the concrete. This study uses the percentage of limestone made with a percentage variation from 0% to 15% (0%, 1%, 5%, 10%, and 15%) of the volume of cement based on experiments (mix design calculations) and for plastic waste with a percentage variations from 0% to 10% (0%, 1%, 5%, and 10%) of the crude aggregate volume based on my experiment (mix design calculations). The concrete is molded by using 4 cylindrical molds measuring 15cmx30cm for each test concrete quality. The compressive strength will be tested at the age of 14 and 28 days. The results of the research on concrete with additional substitution in the form of lime which was substituted into cement and plastic waste substituted for crude in coarse agrrates tended to experience a decrease in quality or compressive strength when compared to normal concrete without any added substitute materials. Research on the highest compressive strength value of concrete mixed with substitution material is the mixture or variation A (1% + 1%) with the average results of 20.27Mpa.